(untitled) (Journal of Psychiatrists’ Association of Nepal, 2017)
Introduction: Schizophrenia is one of the severe mental health problem and its guarded treatment response and association with as the stigma makes it a chronic debilitating personal, family and social problem of all the psychiatric illness. Timely Identification and management of this condition is important as early diagnosis and management gives better treatment response. Methods: This is a descriptive study done in patients attending psychiatry OPD of Nepalgunj Medical College, Kohalpur for 12 months from June 2013 to May 2014. Results: Out of the 86 study subjects (n=86), males were 54 in number followed by 32 females. The most common age group was 21-40 years representing 46(53.4%), followed by 41-60 years 24(28%), <20 years 12(13.9%) and >60 years 4(4.7%). The most common first contact of the patient with schizophrenia was with faith healers 54 (62.8%) followed by consultation with psychiatrist 18(20.9%). Among the study population, 38(44.2%) visited to the psychiatrist after >41 weeks of the beginning of the illness followed by 34(39.5%) visited in <10 weeks of the beginning of the schizophrenia. Conclusions: Faith healers were the most common first contact person for the patients with schizophrenia followed by psychiatrist . Most of the schizophrenia patients come to psychiatrist after 40 weeks of their illness.